Effectiveness of Ozone Treatment and Packaging Techniques in Preserving Taiwanese Domestic Beef During Refrigerated Storage - Chao-Wei Huang; Shiro Takeda; Yen-Po Chen; Fu-Yuan Cheng; Pei-Jung Wu; Liang-Chuan Lin; Yu-Tse Liu (Foods)
This study investigates the efficacy of ozone treatment combined with different packaging methods on the preservation of Taiwanese domestically produced beef during refrigerated storage. The preservation of fresh beef is crucial for ensuring food safety and quality; we do not know whether changing the packaging method can mitigate the negative effects of ozone on meat and even enhance its positive impact. Beef samples were treated with ozone and packaged using the vacuum or PVDC-tray methods, then stored at 4 °C for 7 days. The results show that ozone treatment effectively inhibited microbial (total plate count, Salmonella, and Escherichia coli) growth (p < 0.05). Vacuum packaging maintained lower TBARS values (p < 0.05) and metmyoglobin percentages compared to PVDC-tray packaging (p < 0.05). The L* values of all treatments increased over storage time, with significant differences observed between days 0 and 7. Ozone treatment combined with vacuum packaging demonstrated promising results in inhibiting microbial growth and preserving beef quality during refrigerated storage. These findings contribute to enhancing the safety and shelf life of Taiwanese domestically produced beef, potentially benefiting both producers and consumers.